A key for identification of rock-forming minerals in thin section - Barker, Andrew J. (Balkema Book, 2014)
"The key for identification of rockforming minerals provides an efficient and systematic approach to identifying minerals in thinsection. It is structured in the form of a dichotomous key, comparable to those widely used in botany and entomology. The present key gives a unique solution for each mineral. The key covers more than 150 of the most commonly encountered rockforming minerals, plus a few rarer but noteworthy minerals, indicative of particular conditions. Illustrated in full colour, with high quality photomicrographs of each mineral, it also provides the most comprehensive atlas of rock-forming minerals currently available."--